Early-life Circumstances Predict Measures of Trust among Adults: Evidence from Hunger Episodes in Post-War Germany - Maximiliane Hörl; Iris Kesternich; James P. Smith; Joachim Winter (Center for Economic Studies and ifo Institute (CESifo), 2016)
Can a major shock in childhood permanently shape trust? We consider a hunger episode in Germany after WWII and construct a measure of hunger exposure from official data on caloric rations set monthly by the occupying forces providing regional and temporal variation. We correlate hunger exposure with measures of trust using data from a nationally representative sample of the German population. We show that individuals exposed to low caloric rations in childhood have significantly lower levels of trust as adults. This finding highlights that early-life experiences can have long-term effects in domains other than health, where such effects are well-documented.
Keywords: D01; D74; J10; J62; N44; Z13; 330; trust; endogenous preferences; hunger; war